Psychological Distress of Healthcare Workers in 4 Hospitals Compared to General Population During the First Italian Wave of COVID-19 Pandemic - Gianmarco Russo MD; Marianna N Vargas MD; Vittorio Santoro MD; Maria Ginevra Oriani MD; Astrid Focosi MD; Ilaria Capecci MD; Giuseppe Servillo MD; Stefania De Simone PhD; Maria Vargas MD (SAGE Publishing, 2023)
COVID-19 caused important consequences on public health, economy, physical, and mental health of people. The aim of this study was to evaluate the impact of COVID-19 on frontline workers, comparing them with their colleagues who had no contact with the patients and with the general population, by administering an online questionnaire based on the Distress Questionnaire-5 (DQ5). The study was carried out during the first Italian wave of COVID-19 pandemic from 1st to 30th of April. Participants were divided in 3 groups: group 1 is general population group that includes the general population which are quarantined but not isolated, group health care staff not working in COVID-19 hospitals, and group 3 healthcare staff group working in COVID-19 hospitals. The survey was carried with the Distress Questionnaire-5 (DQ5) as a tool to detect the psychological distress and mental health problems. A total of 2983 people participated in this survey. Seven hundred and twenty four out of 1123 (64%) were employers of the 4 hospitals included in this study. Particularly among the respondents, 2259 (75.7%) were general population, 502 (16.8%) were health care staff not working in COVID-19 hospitals, while 222 (7.4%) were health care staff working in covid-19 hospitals. Health care personnel working in COVID-19 hospitals (DQ-5 = 13, 10-16) had less psychological distress compared with health care staff not working in COVID-19 hospitals (DQ-5 = 14, 11-16) and general population (DQ-5 = 14, 11-17; P  = .04). The regression model showed that people aged 26 to 35 (OR: 2.06, 95% CI: 1.21-3.48) and female (OR: 2.35, 95% CI: 1.95-2.83) were significantly at risk to develop a DQ-5 ≥ 11. During the first Italian wave of COVID-19 pandemic, healthcare personnel working in COVID-19 hospitals had less psychological distress compared with health care staff not working in COVID-19 hospitals and general population, probably because they were prepared to face situations like outbreak or emergencies.